IMPROVING STRUDENTS ACTIVITY USING QUESTION AND ANDSWER METHOD ON 7TH GRADE STUDENTS ARABIC SUBJECT - Yilweri, Yilweri (Universe, 2023)
Learning Arabic using the question and answer method can increase student activity in Arabic learning activities in 7th grade MTsN 7 Solok. Based on this research, the learning activities of students in the second cycle have reached an average of 62% asking questions, 68% answering questions, and 63% giving responses. Judging from the fact that the average learning activity of students from cycle 1 to cycle 2 has increased. In asking questions there was an increase of 30%, answering questions increased by 30% and giving responses increased by 35%. Thus it can be concluded that learning using the question and answer method can increase the learning activities of students in learning Arabic in 7th grade MTsN 7 Solok.